Developing an interactive and illustrative laboratory management curriculum for cytopathology trainees. Issue 10 (22nd July 2020) - Lepe, Marcos; Preciado, Christopher; Song, Sharon J.; Baloch, Zubair W.
Abstract: Laboratory management is a critically important but often overlooked portion of cytopathology training. Indeed, recent surveys of new‐in‐practice pathologists have consistently shown this to be an area of deficiency. Fortunately, there are a multitude of resources available to fill this need. 1‐6 These resources, such as government websites and publications by professional organizations, are often freely accessible to everyone; however, the information they provide is scattered across the vast expanse of cyberspace. We offer this educational module to bridge those gaps and string together a web of resources. The curriculum content includes a pretest to assess the trainee's knowledge and a tree of clickable subject headings covering basic laboratory management topics that a graduating cytopathology fellow should be familiar with. Each subject heading is linked to a summary of the subject using tables and visual diagrams with hyperlinks to specific online resources and additional detailed information. A posttest is included to provide instant feedback. Although by no means comprehensive, we hope this will provide a stepping stone for our readers to build a sound laboratory management foundation that may guide their practice.